Peningkatan Pengetahuan Masyarakat Melalui Sosialisasi Pengolahan Limbah Kopi Di Nagari Unggan Oleh Mahasiswa KKN Universitas Negeri Padang - Purwantono; Yohana; Lestari Febriani; Tia Anggraini Tasty; Fauziah Putri Perdana (CV. SINAR HOWUHOWU, 2025)
Unggan is one of the villages in Sumpur Kudus Subdistrict, Sijunjung District, known as a coffee-producing region. It has many farmers and produces high-quality coffee, but unfortunately, the community in Unggan still lacks proper coffee waste management. Especially coffee husk waste, which has not been fully utilized by the village community. In fact, this coffee waste can be turned into useful products such as compost fertilizer. Therefore, this community service activity was conducted to enhance the villagers' understanding of the potential of coffee husk waste as an alternative resource, while equipping them with the skills and knowledge to process it into high-quality organic compost. In addition to addressing waste management, the program aims to improve agricultural productivity, enhance the standard of living for the community, and support the environmental conservation movement being promoted by the government and the global community. The method used in this activity is through socialization. Composting coffee husks is a smart way to reduce the negative impact of waste on the environment and improve soil quality sustainably.